Pendekatan QFD dalam Perancangan Alat Angkut Cangkang Buah Sawit yang Ergonomis - Nofirza Nofirza; Supardi Supardi (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
The transfer of palm fruit shells from the storage space to the conveyor of chain grate stoker in PT. Sari Lembah Subur II was done manually using traditional cart and shovel. The unergonomic position of operator during this task, the repetitive motions and the difficulties of shells casting to the conveyor made this task having a high work load. This research aimed to produce an ergonomic material handling for palm fruit shells based on operator needed. With the Quality Function Deployment approach, the House of Quality of material handling specification needed was built. The design proceed has done with the combination of operator appropriate antropometric data.The result showed the designed of material handling can give a big contribute to minimized the problem persisted like the ergonomic position of operator during the task, the procces to handling the shells become more simple, no need additional tools, and also minimizing the operator.Keywords: antropometric, chain grate stoker, ergonomic, material handling, QFD